Proposal of desining a portal to manage digital arabic content - ALOUI, Hind; MESROUA, Mahmoud (Journal of Human Sciences, 2020)
Digital content has become one of the most important elements of the business model in the age of the information economy. Proper attention to this type of content has become crucial to the success of organizations. Academic organizations, as any other organization, need Web portals to publish and manage their digital content in order to satisfy the needs of the academic staff, and students. Arabic academic organizations face many challenges in managing their digital content, mainly the lack of an adequate platform for publishing this content.